2021
DOI: 10.1111/ene.15128
|View full text |Cite
|
Sign up to set email alerts
|

Vessel wall magnetic resonance imaging in COVID‐19‐associated cryptogenic ischemic stroke

Abstract: Background and purpose Acute ischemic stroke (AIS) is a common complication of coronavirus disease 2019 (COVID‐19), but the underlying biological mechanisms remain unclear. We aimed to describe the prevalence of vessel wall alterations in patients with cryptogenic stroke through vessel wall magnetic resonance imaging (vwMRI). Methods All consecutive patients admitted for AIS and COVID‐19 to a single neuro‐COVID unit from 10 November to 31 December 2020 were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In 2 reported cases of SARS-CoV-2-related stroke in children, 1 with arteritis (also included in this cohort) and 1 with focal cerebral arteriopathy, vessel wall imaging demonstrated enhancement, which further supports an inflammatory mechanism of SARS-CoV-2-related arteriopathies, 8 , 10 and this mirrors findings in adults. 24 The hemorrhagic transformation present in 1 child with arteritis may reflect endotheliitis-related vessel fragility. Furthermore, patients with MIS-C present with a different inflammatory milieu than those with COVID-19, 25 , 26 and MIS-C may also contribute to cases of arteriopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 reported cases of SARS-CoV-2-related stroke in children, 1 with arteritis (also included in this cohort) and 1 with focal cerebral arteriopathy, vessel wall imaging demonstrated enhancement, which further supports an inflammatory mechanism of SARS-CoV-2-related arteriopathies, 8 , 10 and this mirrors findings in adults. 24 The hemorrhagic transformation present in 1 child with arteritis may reflect endotheliitis-related vessel fragility. Furthermore, patients with MIS-C present with a different inflammatory milieu than those with COVID-19, 25 , 26 and MIS-C may also contribute to cases of arteriopathy.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Guggenberger et al 15 argued that the reported VWI findings by Uginet et al were also possibly due to enhancement associated with intracranial vasa vasorum, developing with advancing age, seen in their own cohort with no clinical or laboratory features of vasculitis. Another study by Mazzacane et al 16 reported concentric vessel wall thickening and enhancement of the involved arterial territories, with associated stenosis and/or occlusion on MRA and cerebral angiography, of patients with COVID-19 deemed to have cryptogenic stroke. We feel that VWI findings that are seen in patients with COVID-19 associated neurological syndromes do not definitively confirm causality, nor do they exclude in total the contributory role of COVID-19 infection in the pathophysiology.…”
Section: Discussionmentioning
confidence: 97%
“…First, intracranial vessel imaging was not standardized and performed in many included patients. Signs of intracranial vessel wall inflammation have been recently described in COV19 + patients with neurological involvement and we were not able to systematically investigate this potential determinant of intracranial bleeding [ 12 , 13 ]. Second, selection bias in favor of less severely affected patients may have occurred, as all the included subjects were not primarily admitted to intensive care or neurosurgery units.…”
Section: Discussionmentioning
confidence: 99%